The Influence of Organizational Culture and Knowledge Management on Innovative Work Behavior through Locus of Control as Mediating Variable (Study on Employees of PT Asuransi Untuk Semua) - Setiawan, Violieta Saviera; Utami, Hamidah Nayati; Ruhana, Ika (Sekolah Pascasarjana Universitas Brawijaya, 2025)
This study aims to examine how Organizational Culture and Knowledge Management (KM) affect Innovative Work Behavior (IWB) and how Locus of Control (LOC) acts as a mediating factor in PT Asuransi Untuk Semua employees. This research can be used by businesspeople, especially in the startup field, to consider implementing innovative employee knowledge in the workplace. This research was conducted on all employees of PT Asuransi Untuk Semua (PT AUS), an insurance startup in Indonesia, who are applying innovation in the form of applications. Using a nonprobability sampling approach, a sample of 150 respondents filled out this research questionnaire using a quantitative approach. Partial Least Squares-Structural Equation Modeling (PLS-SEM) was used to evaluate the data in this study using SmartPLS 4 software. The result of this study is that organizational culture and knowledge management affect innovative work behavior (IWB). Organizational Culture and Knowledge Management affect the locus of control, and LOC mediates the relationship between Organizational Culture and Knowledge Management on IWB. Practical implications can be applied to insurance startups in Indonesia. This research shows that companies must always increase employee innovation and creative work. This can help companies grow and keep up with the development of the Indonesian insurance industry. Keywords: organizational culture, knowledge management, Innovative Work Behavior (IWB), Locus of Control (LOC)